Cisticercose bovina no Estado do Espírito Santo no período de 2009 a 2012: $b análise de registros de matadouros frigoríficos - Falçoni, Fernanda Maria dos Santos de Moraes (2014)
Bovine cysticercosis is a zoonosis found in most post-mortem inspection of slaughtered cattle in Brazil, transmitted to humans by eating raw or undercooked meat containing viable cysts. The aim of this study was to conduct an analysis of records of bovine cysticercosis in slaughterhouses of the state of Espírito Santo in the period 2009-2012. The data relating to convictions carcass and organs were obtained from the Serviço de Inspeção Federal (SIF) and Estadual (SIE) of the state of ES. A total of 1,340,751 cattle during the study period and an average prevalence of 0.84% were slaughtered.The data recorded at the SIF mean prevalence was 0.87 % and the anatomical regions affected were heart, tongue, head and liver, respectively. The data from the SIE, the prevalence was 0.83 % and the most affected organs were the heart, head, liver and tongue, respectively. In every year overall survival of cysts was higher than the number of calcified cysts. Losses for cysticercosis in the period was R$ 9,092,834.97 to pay 1,518,256.8 kg meat. The cases of cysticercosis increased between the years 2010, 2011 and 2012 (p < 0.001 ), showing an increasing trend of the disease and a significant difference between the seasons (p = 0.01), with the rainy season featuring a number most cases of cysticercosis. In a specific study conducted in a slaughterhouse in the southern state, a questionnaire sent to the executors inspection found inability to differentiate cysts of different species of parasites.